An Algorithm for Forefoot Reconstruction With the Innervated Free Medial Plantar Flap. Issue 2 (February 2016) - Zelken, Jonathan A.; Lin, Chih-Hung
Abstract : Background: Because of shearing forces, the forefoot is more prone to trophic ulcers than the heel. Reconstruction of trophic ulcers and other forefoot defects is a vexing challenge. We favor the innervated free medial plantar flap to replace like-with-like and confer protective sensation. We investigate the feasibility of this flap with the largest series to date and the first to describe ipsilateral flap transfer. Methods: Between 2009 and 2013, 7 patients with forefoot defects were treated with innervated free medial plantar flaps. The average age of 4 men and 3 women was 35.1 years (range, 8–50 years). Indications were secondary reconstruction after trauma and coverage of oncologic defects. The mean defect was 5 × 7 cm (range, 4–6 cm × 6–10 cm). Four patients were treated with contralateral flaps and 3 with ipsilateral flaps using interposition vein graft. Results: The mean flap size was 8.1 ± 1.6 cm × 5.9 ± 1.2 cm. There was no perioperative complication, venous congestion, or arterial insufficiency. Patients were followed clinically for 38.5 months (range, 6 months to 10 years). One patient died from complications of metastatic disease 7 months after plantar flap reconstruction. Two patients underwent sensory testing and gait analysis. The appearance was satisfactory, ambulation returned to normal, and there was protective sensation in every case. In 2 cases, hyperkeratotic tissue was excised in revision procedures. Conclusions: The innervated free medial plantar flap is an attractive and feasible option for coverage of medium-to-large defects of the plantar forefoot in the hands of a skilled microsurgeon. It has a place in our algorithmic approach to forefoot reconstruction.